If women counted: A new feminist economics - Waring, Marilyn (Harper & Row, 1988)
This is a revolutionary and powerfully argued feminist analysis of modern economics, revealing how woman's housework, caring of the young, sick and the old is automatically excluded from value in economic theory. An example of this pervasive and powerful process is the United Nation System of National Accounts which is used for wars and determining balance of payments and loan requirements.
Keywords: OFDIG; approches et analyses; discipline; femmes*; inégalités; sciences de la gestion; systèmes d'oppressions; thématiques; travail; économie